2020
DOI: 10.1101/2020.05.13.092833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insulin receptor activation by proinsulin preserves synapses and vision in retinitis pigmentosa

Abstract: Synaptic loss, neuronal death, and circuit remodeling are common features of central nervous system neurodegenerative disorders. Retinitis pigmentosa (RP), the leading cause of inherited blindness, is a group of retinal dystrophies characterized by photoreceptor dysfunction and death. The insulin receptor, a key controller of metabolism, also regulates neuronal survival and synaptic formation, maintenance, and activity. Indeed, deficient insulin receptor signaling has been implicated in several brain neurodege… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Our findings underscore the importance and feasibility of targeting common pathways as a therapeutic strategy for the global treatment of the multiple varieties of RP caused by distinct mutations. We previously demonstrated that multi-faceted neuroprotective drugs can provide structural and functional benefits in several RP animal models [ 48 , 49 , 50 , 51 ]. Here, we show that the targeting of Tlr2 has a disease-modifying effect in RP, regardless of the causative mutation; thus validating TLR2 as a potential therapeutic target for RP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings underscore the importance and feasibility of targeting common pathways as a therapeutic strategy for the global treatment of the multiple varieties of RP caused by distinct mutations. We previously demonstrated that multi-faceted neuroprotective drugs can provide structural and functional benefits in several RP animal models [ 48 , 49 , 50 , 51 ]. Here, we show that the targeting of Tlr2 has a disease-modifying effect in RP, regardless of the causative mutation; thus validating TLR2 as a potential therapeutic target for RP treatment.…”
Section: Discussionmentioning
confidence: 99%